Biochar reduces soil heterotrophic respiration in a subtropical plantation through increasing soil organic carbon recalcitrancy and decreasing carbon-degrading microbial activity. (July 2018) - Li, Yongchun; Li, Yongfu; Chang, Scott X.; Yang, Yunfeng; Fu, Shenglei; Jiang, Peikun; Luo, Yu; Yang, Meng; Chen, Zhihao; Hu, Shuaidong; Zhao, Mengxing; Liang, Xue; et al.
Abstract: Carbon (C) storage in forest soils can be enhanced through increasing organic C input and decreasing soil heterotrophic respiration (RH ). The inhibitory effect of biochar on RH has been extensively studied in agricultural soils, while such an effect and the mechanisms involved remain unknown in forest soils. Here, we examine the response of soil physicochemical and microbial properties to biochar application and how these factors mediate the biochar-induced change in soil RH in a subtropical bamboo plantation. Our results showed that biochar application significantly reduced RH, and markedly altered most of the studied soil properties important for RH in the bamboo plantation. Biochar application did not affect soil temperature and no relationship between soil RH and either soil moisture or labile organic C content was observed, excluding the possibility that biochar reduced the RH through changing soil temperature, moisture or labile organic C content, factors commonly considered to control RH . As compared to the control, biochar application significantly increased the aromatic C content and RubisCO enzyme activity, while decreased β-glucosidase and cellobiohydrolase (CBH) activities. In addition, the soil RH was positively ( P < 0.01) correlated with β-glucosidase and CBH activities, while negatively ( P < 0.05) correlated with RubisCO enzyme activity. Further, using structural equation modelling, we revealed that bicohar reduced RH through increasing the proportion of soil recalcitrant C fraction and decreasing the β-glucosidase and CBH activities in relation to the decomposition of carbohydrates and celluloses in the soil. This is the first report that increased soil organic C recalcitrancy and decreased activities of C-degrading enzymes are responsible for biochar to reduce RH in the subtropical plantation, which may be key to regulating RH in subtropical plantations through forest management. Graphical abstract: Image 1 Highlights: Biochar reduced soil heterotrophic respiration (RH ) in a bamboo plantation. Biochrar altered most of the studied soil properties important for RH . Biochar reduced RH not via changing soil temperature, moisture or labile organic C content. Biochar reduced RH via changing soil organic carbon recalcitrancy and microbial activity.